On farm studies on oestrus synchronization in cows and buffaloes - PHADNIS, Y P; BHOSREKAR, M R; MANGURKAR, B R (The Indian Journal of Animal Sciences, 2013)
Oestrus synchronization studies undertaken in farmers herds included 371, 256 and 304 crossbreds, local cows and buffaloes respectively. Amongst the animals included in the treatments 60% crossbreds, 57% local cows and 52% buffaloes were cyclie and the rest were anoesturs. Oestrus sychronization lreatments used were the use of PGF 2 alpha PRID and Synchromate B (Implant), following the standard protocol. The inseminations were performed at fixed time intervals, Posttreatments. Manifestation of heat in implant PG-treated groups was poor (87 to 95%) as compared to PRID and treated animals, where it was 96 to 98% abd 95 to 100%,respectively, irrespective of breed and species. The overall least-square mean of the conception rate was 45.47% Â± 09.10. The effect of breed, season breed x treatment and treatment x season were statistically nonsignificant. The effects of treatment and breed x season interction were statistically significant. The conception rates obtained after PGF2 alpha treatment were significantly lower as compared to those observed after PRID or Implant treatments. The conception rates were lowest in summer in buffaloes. Cows showed highest conception rates in summer.